Amyloid-? dimers in the absence of plaque pathology impair learning and synaptic plasticity - Mueller-Schiffmann, Andreas; Herring, Arne; Abdel-Hafiz, Laila; Chepkova, Aisa N.; Schaeble, Sandra; Wedel, Diana; Horn, Anselm; Sticht, Heinrich; Silva, Maria A. De Souza; Gottmann, Kurt; Sergeeva, Olga A.; Huston, Joseph P.; et al. (Brain, 2016)
Despite amyloid plaques, consisting of insoluble, aggregated amyloid-? peptides, being a defining feature of Alzheimer's disease, their significance has been challenged due to controversial findings regarding the correlation of cognitive impairment in Alzheimer's disease with plaque load. The amyloid cascade hypothesis defines soluble amyloid-? oligomers, consisting of multiple amyloid-? monomers, as precursors of insoluble amyloid-? plaques. Dissecting the biological effects of single amyloid-? oligomers, for example of amyloid-? dimers, an abundant amyloid-? oligomer associated with clinical progression of Alzheimer's disease, has been difficult due to the inability to control the kinetics of amyloid-? multimerization. For investigating the biological effects of amyloid-? dimers, we stabilized amyloid-? dimers by an intermolecular disulphide bridge via a cysteine mutation in the amyloid-? peptide (A?-S8C) of the amyloid precursor protein. This construct was expressed as a recombinant protein in cells and in a novel transgenic mouse, termed tgDimer mouse. This mouse formed constant levels of highly synaptotoxic soluble amyloid-? dimers, but not monomers, amyloid-? plaques or insoluble amyloid-? during its lifespan. Accordingly, neither signs of neuroinflammation, tau hyperphosphorylation or cell death were observed. Nevertheless, these tgDimer mice did exhibit deficits in hippocampal long-term potentiation and age-related impairments in learning and memory, similar to what was observed in classical Alzheimer's disease mouse models. Although the amyloid-? dimers were unable to initiate the formation of insoluble amyloid-? aggregates in tgDimer mice, after crossbreeding tgDimer mice with the CRND8 mouse, an amyloid-? plaque generating mouse model, A?-S8C dimers were sequestered into amyloid-? plaques, suggesting that amyloid-? plaques incorporate neurotoxic amyloid-? dimers that by themselves are unable to self-assemble. Our results suggest that within the fine interplay between different amyloid-? species, amyloid-? dimer neurotoxic signalling, in the absence of amyloid-? plaque pathology, may be involved in causing early deficits in synaptic plasticity, learning and memory that accompany Alzheimer's disease.
EVALuna2:26292